2006
DOI: 10.1097/01.shk.0000196498.57306.a6
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4, Nitric Oxide, and Myocardial Depression in Endotoxemia

Abstract: The molecular mechanisms that mediate gram-negative sepsis-associated myocardial dysfunction remain elusive. Myocardial expression of inflammatory mediators is Toll-like receptor 4 (TLR4) dependent. However, it remains to be elucidated whether TLR4, expressed on cardiac myocytes, mediates impairment of cardiac contractility after lipopolysaccharide (LPS) application. Cardiac myocyte contractility, measured as sarcomere shortening of isolated cardiac myocytes from C3H/HeJ (with nonfunctional TLR4) and C3H/HeN (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
58
3
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 40 publications
9
58
3
6
Order By: Relevance
“…TLR4 is part of a receptor complex recognizing Gram-negative bacterial endotoxin and is required for endotoxin signal transduction (29). Experiments with TLR4 inhibitors demonstrated a reduced myocardial dysfunction in endotoxinaemia (28,30,31). Here, we detected an increase in fetal cardiac TLR2 and 4 mRNA levels after systemic administration of endotoxin corresponding to the observations in the adult.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…TLR4 is part of a receptor complex recognizing Gram-negative bacterial endotoxin and is required for endotoxin signal transduction (29). Experiments with TLR4 inhibitors demonstrated a reduced myocardial dysfunction in endotoxinaemia (28,30,31). Here, we detected an increase in fetal cardiac TLR2 and 4 mRNA levels after systemic administration of endotoxin corresponding to the observations in the adult.…”
Section: Discussionsupporting
confidence: 52%
“…Apart from iNOS, members of the TLR family, TLR4 in particular, are also thought to mediate the endotoxinaemic myocardial dysfunction in adult sepsis patients (28). TLR4 is part of a receptor complex recognizing Gram-negative bacterial endotoxin and is required for endotoxin signal transduction (29).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that the binding of LPS to TLR4 on rat CMs clearly contributes to myocardial depression (41). We now provide evidence that similar pathways are activated following thermal injury, leading to impaired cardiac contractility.…”
Section: Discussionmentioning
confidence: 55%
“…Massive stimulation of the TLRs by N. meningitidis, emphasized by the local septic thrombi and increased concentration of N. meningitidis lipopolysaccharide (LPS) analog due to endothelium adherence of the bacteria, could generate such antigenic stimulation, resulting in strong innate immune signaling and myocardial dysfunction. Polynuclear infiltration of the myocardial muscle has been demonstrated to be of critical importance in the TLR4-mediated contractile dysfunction induced by sepsis (26,27). Polynuclear infiltration is present in almost 20% of the vessels analyzed in our model and may also participate in myocardial dysfunction.…”
Section: Discussionmentioning
confidence: 81%